2004
DOI: 10.1116/1.1722656
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition behavior of reactive sputtering deposited Co–N thin films using transmission electron microscopy

Abstract: Cobalt nitride thin films could be prepared by employing a direct current reactive sputtering deposition on (100) silicon substrates in mixtures of fixed Ar (4×10−1 Pa) and N2 at various partial pressures. The CoxN thin films could be tailored by appropriately controlling the partial pressure of the reactive nitrogen. With adequately increasing nitrogen to argon partial pressure, a series of sequence phase formation from α-Co, Co4N, Co3N, Co2N, and CoN could be observed. The phase transition sequence was accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…The XRD patterns of Co 4 N and Co 4 N/c-Al 2 O 3 are consistent with those reported in the literature for pure Co 4 N [22]. Fang et al [20] reported that the grain structure of Co 4 N is similar to that of Co. We also found that it is impossible to differentiate Co 4 N from Co because the XRD pattern of Co 3 O 4 reduced in H 2 at 700°C for 2 h looks exactly the same as that of Co 4 N ( Fig. 1).…”
Section: Catalyst Regenerationsupporting
confidence: 89%
See 1 more Smart Citation
“…The XRD patterns of Co 4 N and Co 4 N/c-Al 2 O 3 are consistent with those reported in the literature for pure Co 4 N [22]. Fang et al [20] reported that the grain structure of Co 4 N is similar to that of Co. We also found that it is impossible to differentiate Co 4 N from Co because the XRD pattern of Co 3 O 4 reduced in H 2 at 700°C for 2 h looks exactly the same as that of Co 4 N ( Fig. 1).…”
Section: Catalyst Regenerationsupporting
confidence: 89%
“…CoN ? Co [20]. Kojima and Aika investigated the use of Re 3 N as catalysts for ammonia synthesis (623 K and 0.1 MPa).…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al [38] have reported the stepwise decomposition of Co 4 N via Co 3 N to Co 2 N upon thermal annealing thin films of cobalt nitride. The preparation of cobalt nitride was found to be challenging with formation possibly only being achieved within a narrow temperature window.…”
Section: Resultsmentioning
confidence: 99%
“…At each given temperature, the reaction was allowed to stabilize for 1 h. The products of hydrazine decomposition, i.e., NH 3 , N 2 , H 2 and any unconverted N 2 H 4 , were detected by an on-line gas chromatograph equipped with a TCD detector (Agilent 6890A with 13X and Chromosorb 103 columns). [22]. It is also noted that the diffraction peaks of the Co 4 N-Al 2 O 3 (HT) sample are much broader than those of the Co 4 N/Al 2 O 3 (IMP).…”
Section: Hydrazine Decompositionmentioning
confidence: 93%